Optimización de la gestión en empresas de consultoría mediante Lean Office para la reducción de retrabajos - Javier Gonzales, Daniela Regina (2025)
In Peru, the service sector employs 43% of the economically active population (EAP), demonstrating its importance to the national economy. This research proposes a management model based on Lean Office tools to reduce the rework rate in a consulting SME specializing in ERP. A mixed methodology is used, including service analysis, interviews with executives, and Arena® simulations. The results project a reduction in rework from 75% to 25% and a 30% improvement in delivery times. The main root causes identified include errors in the technical proposal, deficiencies in task scheduling, and defects in deliverables. The proposal includes the standardization of procedures based on PMBOK guidelines and the implementation of the 5S tool in digital environments, guiding management toward continuous improvement, operational efficiency, and service quality.